Social participation in water resource management: Reality of the Center Hydrographic Region Council (Portugal) and the Apodi-Mossoró River Basin Committee (Brazil) - Pinto Filho, Jorge Luís de Oliveira; Cunha, Lúcio (GOT: Revista de Geografia e Ordenamento do Território, 2024)
Research Purpose: Water is a natural resource essential to human development, with multiple uses, which generates pollution processes, with environmental, economic, and social consequences. This work aims to evaluate the social participation in the management of water resources in Portugal and Brazil. Methodology: For this, we adopted the methodological procedures of systematic literature review, investigation of the documentation on the Council of the Hydrographic Region (CRH) of Center/Portugal and the Hydrographic Basin Committee (CBH) of the Apodi/Mossoró River in Brazil and obtaining field data with the application of interviews to the members of these two institutions. Findings: It was found that the participation of the members of CRH Center/Portugal and the CBH of the Apodi/Mossoró River in Brazil refers to the similarities in the degree of participation, diversity of the segment, number of members, participation of civil society, and participation of the private sector; however, they are distinct concerning the degree of interest, ways of choosing the members, their level of knowledge, the interaction between the members and the participation of the public authorities. Originality/Value: Therefore, it is recommended for the evolution of these management models a deeper knowledge of their representatives, through the diagnosis of the socioeconomic profile, as well as their environmental perception.